Study on the Effect of 4D-CT Special Reconstruction Images for Evaluation of the Cardiac Structure Dose in Radiotherapy for Breast Cancer - Su, Ming; Gong, Guanzhong; Qiu, Xiaoping; Tong, Ying; Li, Qian; Yin, Yong (Frontiers in Oncology, 2020)
Objective To study the dosimetric effect on special reconstruction images obtained from an electrocardiograph-gated four-dimensional computed tomography (ECG 4D-CT) series and compare it with the accumulation dose assessment of ECG 4D-CT. Methods Fifteen patients underwent ECG 4D-CT scans to obtain a 4D-CT series. The 20 phase images of 0%~95% were reconstructed at intervals of 5% of the cardiac cycle by the 4D-CT series. The 4D-CT series was specially reconstructed, and the maximum intensity projection (MIP), minimum intensity projection (MinIP), average intensity projection (AIP) and sum intensity projection (SIP) were obtained. The left ventricular muscle (LV)and the anterior descending branch of the left coronary artery (LAD) were delineated on all series. The intensity-modulated radiation therapy (IMRT) plan for left breast cancer was designed on the basis of the 0% phase, and the accumulative dose (Dose-acc) of 20 phases was obtained by deformation registration. The dose-volume indexes of the LV and LAD were compared based on different CT series. Results The dose-volume indices of V5, V30, V40, Dmax and Dmean of the LV on MIP images were 3.8%, 2.0%, 0.9%, 3.8% and 1.7%, respectively (relative to the Dose-acc). There was no significant difference in V5 or Dmax between the MIP and Dose-acc (P>0.05). The change rates of Dmax on the MinIP, SIP and AIP images were 2.5%, 3.1% and 1.5%, respectively (relative to the Dose-acc) (P<0.05). Conclusion In the dose-volume evaluation of the LV, V30, V40 and Dmean obtained by MIP were essentially the same as those obtained by the Dose-acc and can be used instead of the 4D-CT series to evaluate dose-volume indexes.